Lytic Activity of Polyvalent Staphylococcal Bacteriophage PhiSA012 and Its Endolysin Lys-PhiSA012 Against Antibiotic-Resistant Staphylococcal Clinical Isolates From Canine Skin Infection Sites - Nakamura, Tomohiro; Kitana, Junya; Fujiki, Jumpei; Takase, Masayuki; Iyori, Keita; Simoike, Kenta; Iwano, Hidetomo (Frontiers in Medicine, 2020)
The spread of antibiotic-resistant bacteria (ARB) in human and veterinary medicine is of global concern. Notably, the emergence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) has become a serious problem. In this context, bacteriophages and their lytic enzymes, endolysins, have received considerable attention as therapeutics for infectious diseases in place of antibiotics. The aim of the present study was to investigate the antibiotic-resistance patterns of staphylococcal species isolated from canine skin at a primary care animal hospital in Tokyo, Japan and evaluate the lytic activity of the staphylococcal bacteriophage phiSA012 and its endolysin Lys-phiSA012 against isolated antibiotic-resistant staphylococcal strains. Forty clinical staphylococcal samples were isolated from infection sites of dogs (20 from skin and 20 from the external ear canal). Susceptibility to antimicrobial agents was determined by a disk diffusion method. The host range of phiSA012 was determined by using a spot test against staphylococcal isolates. Against staphylococcal isolates that showed resistance toward five classes or more of antimicrobials, the lytic activity of phiSA012 and Lys-phiSA012 was evaluated using a turbidity reduction assay. Twenty-three S. pseudintermedius, 16 Staphylococcus schleiferi and 1 Staphylococcus intermedius were detected from canine skin and ear infections, and results revealed 43.5% methicillin-resistance in S. pseudintermedius and 31.3% in S. schleiferi. In addition, the prevalence of MDR S. pseudintermedius was 65.2%. PhiSA012 could infect all staphylococcal isolates by spot testing, but showed little lytic activity by turbidity reduction assay against MDR S. pseudintermedius isolates. On the other hand, Lys-phiSA012 showed lytic activity and reduced significantly the number of staphylococcal colony forming units. These results demonstrated that ARB issues underlying in small animal hospital and proposed substitutes for antibiotics. Lys-phiSA012 has broader lytic activity than phiSA012 against staphylococcal isolates; therefore, Lys-phiSA012 is a more potential candidate therapeutic agent for several staphylococcal infections including that of canine skin.